Uso do método simplificado de cargas (SLM – IEC 61400-2) e do espectro de cargas de fadiga para estimativa de vida em pás de aerogeradores de pequeno porte - Coimbra, Rodrigo Vacari (2019)
The life of small wind turbine blades applied for electrical energy generation using wind is directly related to its fatigue resistance. Under normal condition operation blades are exposed to cyclic loads as a function of wind velocity variation and, consequently, different mechanical solicitation. The present work aims to estimate the number of cycles inducing fatigue in small wind turbine blades applying the Simple Load Method (SLM) as recommend by IEC 61400-2 standard and the fatigue load spectrum proposed by Epaarachchi (2002). The methodology consisted firstly in characterizing polyamide reinforced fiber glass composite blades in relation to their structures and mechanical properties (tensile strength, bend strength and hardness). Wind data collected in Rio Grande do Sul from May/2009 to May/2011 by INPE – “SONDA Project” were compiled using Weibull’s probabilistic distribution. SLM was applied to convert wind data into load acting on the blades. Epaarachchi’s method was used to determine the fatigue load spectrum as a function of wind velocity and estimate the number of cycles inducing fatigue failure. With results from tensile, bend and hardness tests, wind data converted into mechanical solicitation and the application of life cycle fatigue method, it was possible to estimate two scenarios: (a) Under normal operation (overall wind spectrum) and (b) under critical operation (wind data in the range of 2 m/s to 5 m/s). In the normal scenario the total cycles until the fatigue failure was of 1,554,832 whereas in the critical scenario the failure occurs of 996,812 cycles.